Attitudes among Public School Teachers during The Implementation of Modular Distance Learning in Philippines - Jayme, Cristina Beltran; Mastul, Al-Rashiff Hamjilani; Alih, Alwida Abdurahman (The Indonesian Institute of Science and Technology Research, 2025)
The COVID-19 pandemic has significantly reshaped the educational landscape, necessitating the implementation of Modular Distance Learning (MDL) in the Philippines. This study investigates the attitudes of public school teachers towards MDL, focusing on their readiness, schools’ preparedness, and the effectiveness of modular instruction. Employing a descriptive quantitative research design, data were collected from 261 public school teachers in Zamboanga City using a survey questionnaire. Results indicate that teachers exhibit a high level of readiness to implement MDL, demonstrating adaptability and willingness to embrace new teaching strategies. Schools also displayed a high level of preparedness, with established communication channels and health protocols. However, challenges persist, particularly regarding the effectiveness of modular instruction, which teachers perceive to be less effective compared to face-to-face learning. Statistical analyses reveal no significant differences in teachers’ attitudes based on demographic factors such as years of experience, educational background, or employment status. However, male teachers reported a higher perception of module effectiveness compared to their female counterparts. The findings underscore the need for continuous professional development and improved module design to enhance learning outcomes. This study contributes to understanding the realities of MDL implementation and provides a basis for future research on improving distance learning strategies.